Tinjauan Letter of Coordination Agreement pada Proses Publikasi Aeronautika di PIA Wilayah Jakarta - Puspitasari, Risma Farhani; Arti, Endang Sugih; Amir, Elfi; Rohmah, Kyky (Jurnal Bisnis dan Operasi Penerbangan, 2025)
LOCA (Letter of Coordination Agreement) is an operational agreement between one party and another. In this research, the author studied the daily activities of a group under natural conditions through observations and interviews. To improve thee quality of aeronautical information data, it necessary to have periodic meetings between AIS Jakarta Regional and data sources to discuss and review issues that are not in accordance with the agreed LOCA.